Perceptions of prognosis in patients with advanced lung cancer: Associations with patient demographics, quality of life, and depression symptoms. Issue 28 (1st October 2022) - Han, Jacqueline; Post, Kathryn Elizabeth; Gallagher-Medeiros, Emily R; Trotter, Chardria; Heuer, Lauren; Plotke, Rachel; Turk, Yael; Rinaldi, Simone; Kamdar, Mihir; Jackson, Vicki A.; Park, Elyse R.; El-Jawahri, Areej; et al.
Abstract : 247 Background: Despite the importance of having a clear understanding of the likely outcome of cancer to inform medical decision-making, about one third of patients with advanced lung cancer report inaccurate perceptions of their prognosis. To identify factors associated with lower and higher prognostic understanding, we examined the relationships among patients' perceptions of prognosis and their demographic characteristics, quality of life (QOL), and mood symptoms. Methods: We conducted a cross-sectional analysis of baseline data from patients enrolled in two multisite palliative care trials. Eligible participants included adults with advanced non-small cell lung cancer, small cell lung cancer, or mesothelioma diagnosed in the past 12 weeks and an ECOG Performance Status <3 across 23 cancer centers in the US. At baseline, patients self-reported their current health status and understanding of whether their cancer is curable. Patients' prognostic understanding was categorized into three levels: "high" if patients reported that their illness was terminal and incurable, "medium" if patients reported that their illness was either terminal or incurable, and "low" if patients reported that their illness was neither terminal nor incurable. To assess QOL and depression symptoms, patients completed the Functional Assessment of Cancer Therapy-Lung (FACT-L) and the Patient Health Questionnaire-9 (PHQ-9), respectively. Linear regression models adjusting for patient demographic factors were used to examine the associations among prognostic understanding, QOL, and depression symptoms. Results: The sample included 1430 patients with advanced lung cancer (Mean age = 65.50 years; 52.5% female; 4.0% Asian, 10.6% Black, 81.8% White; 65.9% married). Patient-reported prognostic understanding varied as follows: high (45.1%), medium (32.7%), and low (22.2%). Patients who were older (p =.015), male (p <.001), Black or Asian (p =.015), or married (p =.012) had lower prognostic understanding. Adjusting for demographic factors, patients with higher prognostic understanding reported worse QOL (FACT-L: B = -5.392, SE = 0.71, p <.001) and depression symptoms (PHQ-9: B = 0.99, SE = 0.19, p < 0.001) versus those with lower prognostic understanding. Conclusions: A substantial proportion of patients with newly diagnosed advanced lung cancer have low prognostic understanding. Those with high prognostic understanding report worse QOL and depression symptoms, which may be due to patients relating their poor health status to their prognosis. Furthermore, patient age, gender, race, and relationship status are salient correlates of prognostic understanding. Tailored interventions are needed to improve illness understanding and address the related supportive care needs of patients with advanced lung cancer, especially those at risk for low prognostic understanding.